Evaluation of phototoxicity of dendritic porphyrin-based phosphorescent oxygen probes: an in vitro study - Ceroni, Paola (2011)
Biological oxygen measurements by phosphorescence quenching make use of exogenous phosphorescent probes, which are introduced directly into the medium of interest (e.g. blood or interstitial fluid) where they serve as molecular sensors for oxygen. The byproduct of the quenching reaction is singlet oxygen, a highly reactive species capable of damaging biological tissue. Consequently, potential probe phototoxicity is a concern for biological applications. Herein, we compared the ability of polyethyleneglycol (PEG)-coated Pd tetrabenzoporphyrin (PdTBP)-based dendritic nanoprobes of three successive generations to sensitize singlet oxygen. It was found that the size of the dendrimer has practically no effect on the singlet oxygen sensitization efficiency in spite of the strong attenuation of the triplet quenching rate with an increase in the dendrimer generation. This unexpected result is due to the fact that the lifetime of the PdTBP triplet state in the absence of oxygen increases with dendritic generation, thus compensating for the concomitant decrease in the rate of quenching. Nevertheless, in spite of their ability to sensitize singlet oxygen, the phosphorescent probes were found to be non-phototoxic when compared with the commonly used photodynamic drug Photofrin in a standard cell-survival assay. The lack of phototoxicity is presumably due to the inability of PEGylated probes to associate with cell surfaces and/or penetrate cellular membranes. In contrast, conventional photosensitizers bind to cell components and act by generating singlet oxygen inside or in the immediate vicinity of cellular organelles. Therefore, PEGylated dendritic probes are safe to use for tissue oxygen measurements as long as the light doses are less than or equal to those commonly employed in photodynamic therapy.